2011
DOI: 10.1073/pnas.1016442108
|View full text |Cite
|
Sign up to set email alerts
|

Role of CB1 cannabinoid receptors on GABAergic neurons in brain aging

Abstract: Brain aging is associated with cognitive decline that is accompanied by progressive neuroinflammatory changes. The endocannabinoid system (ECS) is involved in the regulation of glial activity and influences the progression of age-related learning and memory deficits. Mice lacking the Cnr1 gene (Cnr1 −/− ), which encodes the cannabinoid receptor 1 (CB1), showed an accelerated agedependent deficit in spatial learning accompanied by a loss of principal neurons in the hippocampus. The age-dependent decrease in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 51 publications
6
82
0
Order By: Relevance
“…In good agreement with these findings, genetic deletion of CB1 receptors leads to defective neurogenesis [221]. The consequence of this effect on the learning phenotype is unclear but it is unrelated to the early loss of cognitive abilities in this strain [197].…”
Section: (D) Regulation Of Glial Activitysupporting
confidence: 70%
See 2 more Smart Citations
“…In good agreement with these findings, genetic deletion of CB1 receptors leads to defective neurogenesis [221]. The consequence of this effect on the learning phenotype is unclear but it is unrelated to the early loss of cognitive abilities in this strain [197].…”
Section: (D) Regulation Of Glial Activitysupporting
confidence: 70%
“…The peripheral organs also did not show signs of early ageing except in the skin, where an atrophy of the subdermal fat layer was present in 12-month-old CB1 2/2 but not in wild-type mice [5]. A following study showed that the early onset of cognitive decline and neuronal loss was accompanied by neuroinflammatory changes in the hippocampus, but not in the cortex or striatum [197]. It was suggested that CB1 receptors on the GABAergic neurons play a principal role in the regulation of glial activity and thus in protection against age-related changes: deletion of CB1 receptors from the forebrain GABAergic but not glutamatergic neurons resulted in a similar ageing phenotype as found in the constitutive knockouts [197].…”
Section: Age-dependent Effect Of the Cannabinoid System On Learning Amentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, knowing that ajulemic acid induces the release of LXA 4 acting as a proresolving mediator in inflammation (30); that LXA 4 increases the affinity of AEA for the CB 1 receptors (this study); and that certain metabolites of AEA degradation by lipoxygenases retain affinity for the CB 1 receptor (46) or reduce AEA metabolism by FAAH (47), we may hypothesize that LOX derivatives such as LXA 4 might participate in a positive feedback loop sustaining endocannabinoid tonus under certain conditions, for example, brain inflammation (48), epilepsy (49,50), or aging (51). This may be an interesting explanation for the observed neuroprotection against β-amyloid (1-40)-induced memory impairment, which is regarded as an important component of Alzheimer's disease pathophysiology (52).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, A␤ has been demonstrated to inhibit long-term plasticity processes associated with learning and memory through suppression of CB 1 -dependent GABAergic synaptic disinhibition [26]. Moreover, CB 1 receptor activity in GABAergic neurons protects against agedependent cognitive decline [27]. Therefore, it may be speculated that the combination of 9 -THC and CBD facilitates inhibitory GABAergic activity in the somatosensory cortex by mitigating the deleterious effect of A␤ on GABAergic function, and subsequently on cognitive performance, via activation of CB 1 receptors.…”
Section: Discussionmentioning
confidence: 99%